2007
DOI: 10.1002/jcb.21172
|View full text |Cite
|
Sign up to set email alerts
|

Towards in situ tissue repair: Human mesenchymal stem cells express chemokine receptors CXCR1, CXCR2 and CCR2, and migrate upon stimulation with CXCL8 but not CCL2

Abstract: The recruitment of bone marrow CD34- mesenchymal stem- and progenitor cells (MSC) and their subsequent differentiation into distinct tissues is the precondition for in situ tissue engineering. The objective of this study was to determine the entire chemokine receptor expression profile of human MSC and to investigate their chemotactic response to the selected chemokines CCL2, CXCL8 and CXCL12. Human MSC were isolated from iliac crest bone marrow aspirates and showed a homogeneous population presenting a typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
239
3
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 336 publications
(264 citation statements)
references
References 44 publications
10
239
3
5
Order By: Relevance
“…However, in vivo, it is possible that hMSC chemokine receptors encountering cognate ligand(s) could act in a cooperative manner to activate VLA-4 following CD44 engagement. Low-level expression of a restricted repertoire of chemokine receptors, including CXCR1, CXCR2, CCR2, and CCR3, has been variably reported on hMSCs, with minimal chemotactic response to CXCL8 (ligand of CXCR1 and CXCR2) and CCL5 (ligand of CCR3) (39,40). Wherever detected by flow cytometry, CXCR4 expression on hMSCs is typically nominal (41,42) and, where more prominently observed, is always accompanied by relatively low staining intensity (17,41,43).…”
Section: Discussionmentioning
confidence: 99%
“…However, in vivo, it is possible that hMSC chemokine receptors encountering cognate ligand(s) could act in a cooperative manner to activate VLA-4 following CD44 engagement. Low-level expression of a restricted repertoire of chemokine receptors, including CXCR1, CXCR2, CCR2, and CCR3, has been variably reported on hMSCs, with minimal chemotactic response to CXCL8 (ligand of CXCR1 and CXCR2) and CCL5 (ligand of CCR3) (39,40). Wherever detected by flow cytometry, CXCR4 expression on hMSCs is typically nominal (41,42) and, where more prominently observed, is always accompanied by relatively low staining intensity (17,41,43).…”
Section: Discussionmentioning
confidence: 99%
“…19,30 Migration of cells into, or enrichment of, progenitors within the cell-free implant may be induced by autologous serum that contains a variety of chemokines and growth factors. In recent in vitro studies, it has been shown that chemokines and growth factors, 16,31 as well as human synovial fluid 14 and human serum, 24 are potent inducers of mesenchymal stem cell migration. In particular, human serum and blood may be of special interest in cartilage repair, since blood has been shown to improve hyaline cartilage formation after microfracture in a rabbit model when combined with a chitosanglycerol-phosphate implant.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that synovial fluid recruits mesenchymal progenitor cells from bone marrow. 14 In addition, a variety of chemotactic cytokines and growth factors, components of synovial fluid and serum, stimulates migration and homing of mesenchymal stem cells 15,16 and may contribute to ingrowth of progenitors into the cartilage defects in microfracture. Multi-potent cells residing in the subchondral cortico-spongious bone marrow have a high chondrogenic differentiation capacity 17 and may form a cartilaginous repair tissue upon stimulation by growth and differentiation factors from the subchondral bone.…”
mentioning
confidence: 99%
“…21 The results broadly concur with the findings of other investigators who have studied chemokine-induced migration of hMSCs ( Table 1). [22][23][24][25][26][27][28][29][30][31] A notable exception was the failure to demonstrate migration of hMSCs in response to MCP-1 by Ringe et al 26 and CroitoruLamoury et al 22 although the latter did demonstrate chemotaxis following pre-treatment with interferon-β. This apparent discrepancy and the reported variations in the concentration of chemokine triggering migration are likely to be explained by the inhomogeneous nature of hMSC cultures, differences in culture conditions (including passage number) and assay method, as well as donor variability and the level of 'pre-stimulation' of hMSCs.…”
Section: Methodsmentioning
confidence: 99%